Preparation method of anti-freezing sweat-resistant hydrogel with adjustable mechanical modulus
By introducing modified carbon nanotubes and silk proteins into the hydrogel and soaking with 1,2-propylene glycol, the problem of hydrogel losing elasticity at extreme temperatures is solved, achieving mechanical strength and biological in extreme environments Improved compatibility.
Patent Information
- Application Number
- CN202411301525.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
AI Technical Summary
Existing hydrogels are prone to rupture when subjected to physical loads, and lose elasticity or soften deformation under extreme temperature conditions, and their performance decreases in changes in environmental and physiological conditions.
By introducing modified carbon nanotubes and silk proteins into the hydrogel and soaking with 1,2-propylene glycol, it adjusts its mechanical modulus, enhances mechanical strength and biocompatibility, ensuring elasticity and stability at extreme temperatures .
It significantly improves the mechanical strength and biocompatibility of the hydrogel, can maintain physical stability in environments as low as -19°C, and maintain stable performance at temperatures up to 40°C, and is suitable for low and high temperature environments.
Smart Images

Figure CN119161744A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of hydrogel materials, in particular to a method for preparing an antifreeze and sweat-resistant hydrogel with adjustable mechanical modulus. Background Art
[0002] In recent years, in the rapidly developing field of biomedical engineering, hydrogel, as a polymer material with a three-dimensional network structure using water as a dispersion medium, has gradually become an ideal candidate material for human health detection technology. As people's pursuit of healthy quality of life continues to improve, the demand for real-time, non-invasive and accurate health monitoring is becoming increasingly urgent. The application of hydrogel in human health detection has brought great changes to traditional medical detection methods with its excellent biocompatibility, flexibility and fatigue resistance.
[0003] Hydrogels can simulate the biological tissue environment while accurately monitoring physiological parameters. From flexible sensors to wearable devices, from drug delivery systems to electronic skin, the application of hydrogels is gradually penetrating into various fields of human health testing. Through the continuous development and utilization of hydrogel materials, we can not only improve the accuracy of disease diagnosis, but also provide patients with more comfortable and convenient monitoring conditions.
[0004] However, the elastic modulus of existing hydrogels is basically single and fixed, and they are often prone to rupture when subjected to large physical loads due to structural weaknesses. In addition, many hydrogels become brittle and lose elasticity under extreme temperature conditions (especially cold environments), or soften and deform at high temperatures. During long-term storage or repeated use, hydrogels will experience performance degradation due to environmental factors and changes in physiological conditions. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing an antifreeze and sweat-resistant hydrogel with adjustable mechanical modulus. The hydrogel of the present invention significantly improves its mechanical strength and biocompatibility by introducing modified carbon nanotubes and silk protein, and has good long-term stability. At the same time, by soaking in 1,2-propylene glycol, it ensures that it maintains elasticity and does not become brittle at extreme temperatures, resists softening and deformation, and can adjust the modulus as needed, so that it can adapt to complex environmental and physiological conditions.
[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: an antifreeze and sweat-resistant hydrogel with adjustable mechanical modulus, comprising:
[0007] Polyvinyl alcohol: 4% to 8%;
[0008] Acrylic acid: 5% to 10%;
[0009] Silk protein: 8%-15%;
[0010] Modified carbon nanotubes: 0.01% to 0.05%;
[0011] Deionized water: 30% to 40%;
[0012] 1,2-Propanediol: 35%~45%.
[0013] Preferably, the hydrogel further comprises photoinitiator 2959: 0.05% to 0.2%.
[0014] The present invention provides a method for preparing an antifreeze and sweat-resistant hydrogel with adjustable mechanical modulus, comprising the following steps:
[0015] S1. Dissolve polyvinyl alcohol in deionized water and stir to ensure that the polyvinyl alcohol is completely dissolved;
[0016] S2, adding acrylic acid and photoinitiator 2959 to the above solution;
[0017] S3, slowly add silk protein;
[0018] S4, adding the modified carbon nanotube powder into deionized water;
[0019] S5, adding the modified carbon nanotube solution obtained in step S4 to the mixed solution in step S3;
[0020] S6, placing the mixed solution under ultraviolet light to perform a photocuring reaction;
[0021] S7. Soak the photocured hydrogel in 1,2-propylene glycol to adjust and control the mechanical modulus of the final hydrogel.
[0022] Preferably, the S1 step comprises:
[0023] Stirring temperature: 95℃~100℃;
[0024] Stirring time: 1.5 to 2.5 hours.
[0025] Preferably, the S2 step comprises:
[0026] Use magnetic stirring under a warm room to thoroughly mix the acrylic acid and photoinitiator 2959;
[0027] The magnetic stirring time is 25 to 35 minutes.
[0028] Preferably, the S3 step includes:
[0029] Continue to slowly add silk protein under high-speed stirring to ensure that the silk protein is evenly dispersed in the solution;
[0030] High-speed stirring time is: 25 to 35 minutes.
[0031] Preferably, the S4 step comprises:
[0032] Using an ultrasonic device to treat the added modified carbon nanotube powder to obtain a uniformly dispersed modified carbon nanotube solution;
[0033] The processing time of ultrasonic equipment is: 2 to 5 minutes.
[0034] Preferably, the S5 step comprises:
[0035] Mixing the modified carbon nanotube solution and the mixed solution thoroughly under magnetic stirring at room temperature;
[0036] The magnetic stirring time is 25 to 35 minutes.
[0037] Preferably, the S6 step comprises:
[0038] The irradiation power under UV lamp is: 120W~140W;
[0039] The irradiation time is: 0.75 to 1.5 hours.
[0040] Preferably, the S7 step comprises:
[0041] The soaking time is: 1.5 to 18 hours to achieve the desired antifreeze and sweat resistance effects.
[0042] The present invention provides a method for preparing an antifreeze and sweat-resistant hydrogel with adjustable mechanical modulus. The method has the following beneficial effects:
[0043] 1. The present invention significantly improves the strength and elasticity of the hydrogel by adding modified carbon nanotubes and silk protein to the formula. The modified carbon nanotubes enhance the conductivity of the hydrogel, enabling it to improve the response speed of the sensor and the strength of the transmitted signal, while the addition of silk protein provides additional elasticity and toughness, making the hydrogel more suitable for applications that require high elongation and recovery.
[0044] 2. The present invention adds 1,2-propylene glycol as an antifreeze agent to make the hydrogel exhibit excellent antifreeze properties and maintain physical stability and functionality in an environment as low as -19°C, making the hydrogel of the present invention suitable for applications in low-temperature environments. At the same time, it shows good heat resistance and can maintain stable performance at temperatures as high as 40°C, making it suitable for tropical or high-temperature working environments.
[0045] 3. Based on the introduction of silk protein, the hydrogel of the present invention provides good biocompatibility and is suitable for applications that directly contact human skin or other biological tissues. It not only ensures the skin-friendliness of the hydrogel, but also supports cell growth and healing processes, making the hydrogel an ideal choice for medical dressings, drug delivery systems and biosensor devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] The embodiment of the present invention provides an antifreeze and sweat-resistant hydrogel with adjustable mechanical modulus, comprising:
[0049] Polyvinyl alcohol: 4% to 8%. Polyvinyl alcohol, as the main matrix of the hydrogel, provides good elasticity and stability for the hydrogel. It enhances mechanical strength at high concentrations and improves flexibility at low concentrations.
[0050] Acrylic acid: 5% to 10%. Acrylic acid, as a monomer, forms a second hydrogel network during the photocuring process, which can effectively absorb energy and maintain structural stability.
[0051] Silk protein: 8% to 15%. Silk protein is used to form the third network of hydrogel, improve the mechanical properties of hydrogel, provide biocompatibility, and enhance the biological activity of hydrogel. It is suitable for medical and skin contact products.
[0052] Modified carbon nanotubes: 0.01% to 0.05%. Modified carbon nanotubes are used to enhance the conductivity and thermal stability of hydrogels, which are suitable for sensing and heating applications.
[0053] Deionized water: 30% to 40%, used to provide a solvent medium and adjust the overall rheological properties of the hydrogel;
[0054] 1,2-Propanediol: 35%~45%, replaces water in the hydrogel, promotes the entanglement of polymer chains in the hydrogel, adjusts the modulus of the hydrogel, acts as an antifreeze agent, reduces the freezing point of the hydrogel, and enhances the low-temperature resistance.
[0055] In a preferred embodiment of the present invention, the hydrogel also includes a photoinitiator 2959: 0.05% to 0.2%. By absorbing the energy of ultraviolet light, the photoinitiator can effectively initiate the polymerization reaction of acrylic monomers and help form a polymer network, thereby enhancing the structural strength and stability of the hydrogel.
[0056] The present invention also provides a method for preparing an antifreeze and sweat-resistant hydrogel with adjustable mechanical modulus, comprising the following steps:
[0057] S1. Dissolve polyvinyl alcohol in deionized water and stir to ensure that the polyvinyl alcohol is completely dissolved. By stirring, the molecular chains of the polyvinyl alcohol can be fully unfolded and dissolved to form a uniform solution, thereby ensuring the uniformity of the hydrogel matrix and the smooth progress of subsequent chemical reactions;
[0058] S2. Add acrylic acid and photoinitiator 2959 to the above solution. Acrylic acid will participate in the photocuring reaction as a monomer to form a second network of the hydrogel, thereby enhancing the mechanical strength and durability of the hydrogel. Photoinitiator 2959 is the key to starting the photopolymerization reaction, which can effectively absorb ultraviolet light and generate free radicals to initiate the polymerization reaction.
[0059] S3, slowly add silk protein, silk protein can form the third network of hydrogel, enhance the mechanical properties of hydrogel, and have excellent biocompatibility;
[0060] S4, adding the modified carbon nanotube powder into deionized water, wherein the main purpose of adding the modified carbon nanotube powder into the deionized water is to achieve uniform dispersion of the carbon nanotubes;
[0061] S5, adding the modified carbon nanotube solution obtained in step S4 to the mixed solution in step S3, and mixing the modified carbon nanotube solution and the mixed solution, thereby ensuring the uniformity of the components of the hydrogel at the microscopic level and providing a basis for the performance stability of the final product;
[0062] S6, placing the mixed solution under ultraviolet light for photocuring reaction, under ultraviolet light, the photoinitiator generates free radicals, triggering the polymerization reaction of acrylic acid monomers to form a three-dimensional network structure;
[0063] S7. Soak the photocured hydrogel in 1,2-propylene glycol to adjust and control the mechanical modulus of the final hydrogel. 1,2-propylene glycol acts as an antifreeze agent and plasticizer. During the soaking process, it not only adjusts the mechanical modulus of the hydrogel, but also enhances its low temperature and moisture resistance, so that the hydrogel can maintain good performance in low temperature and high humidity environments. It is suitable for applications such as outdoor sports equipment and medical supplies, which improves the practicality of the hydrogel.
[0064] In a preferred embodiment of the present invention, step S1 comprises:
[0065] The stirring temperature is 95℃~100℃. The high temperature accelerates the thermal motion between polyvinyl alcohol molecules, helps to overcome the hydrogen bond interaction between molecules, and promotes its dissolution in water.
[0066] The stirring time is 1.5 to 2.5 hours, which can improve the rheological properties of the solution and make the polyvinyl alcohol molecules easier to unfold and evenly distribute in the solution;
[0067] The uniform polyvinyl alcohol base layer provides a good substrate for the hydrogel, helps to achieve higher mechanical strength and stable mechanical properties, while reducing bubbles and uneven particles that may be formed during the preparation process, so that the final product has better transparency and appearance quality.
[0068] In a preferred embodiment of the present invention, step S2 comprises:
[0069] Use magnetic stirring under a warm room to thoroughly mix the acrylic acid and photoinitiator 2959;
[0070] The magnetic stirring time is 25 to 35 minutes. Magnetic stirring can produce continuous and uniform flow, which helps to quickly disperse and evenly mix the added acrylic acid and photoinitiator. By ensuring the uniform distribution of photoinitiator and acrylic acid, this directly affects the mechanical properties and chemical stability of the hydrogel. The evenly dispersed photoinitiator can absorb ultraviolet light more efficiently during the photocuring process, accelerate the reaction speed, and shorten the curing time.
[0071] In a preferred embodiment of the present invention, step S3 includes:
[0072] Continue to slowly add silk protein under high-speed stirring to ensure that the silk protein is evenly dispersed in the solution;
[0073] The high-speed stirring time is 25 to 35 minutes. Silk protein can form a third network of hydrogel by generating a large number of hydrogen bonds with polyvinyl alcohol and acrylic acid, greatly improving the mechanical properties of hydrogel such as toughness and modulus. Under high-speed stirring, strong mechanical shear force helps to break the interaction between these molecules and promote the uniform dispersion of silk protein in the solution. The uniformly dispersed silk protein can form a more complex three-dimensional network structure with polyvinyl alcohol and acrylic acid. This structure can enhance the overall mechanical strength of the hydrogel and prevent the uneven performance of the hydrogel during use, such as insufficient local strength or uneven water absorption.
[0074] In a preferred embodiment of the present invention, step S4 comprises:
[0075] Using an ultrasonic device to treat the added modified carbon nanotube powder to obtain a uniformly dispersed modified carbon nanotube solution;
[0076] The ultrasonic equipment treatment time is: 2 to 5 minutes. The ultrasonic equipment generates strong local shear force, which can effectively break up the carbon nanotube agglomerates and promote their individual dispersion in the solution. The evenly dispersed carbon nanotubes form a conductive path in the hydrogel matrix, which can more effectively transmit the sensing signal, reduce the signal loss during the transmission process, and improve the stability of the hydrogel sensor.
[0077] In a preferred embodiment of the present invention, step S5 comprises:
[0078] Mixing the modified carbon nanotube solution and the mixed solution thoroughly under magnetic stirring at room temperature;
[0079] The magnetic stirring time is 25 to 35 minutes. During the mixing process of carbon nanotubes and other components, maintaining uniform stirring is the key to preventing carbon nanotubes from reaggregating. Agglomeration will lead to a decrease in material performance, especially in mechanical properties and electrical conductivity. By ensuring that carbon nanotubes are uniformly mixed with other components of the hydrogel such as polyvinyl alcohol and acrylic acid, the mechanical strength and durability of the hydrogel can be improved. The uniform distribution of carbon nanotubes helps to improve its structural integrity and load-bearing capacity, and can also enhance the electrical conductivity of the hydrogel.
[0080] In a preferred embodiment of the present invention, step S6 comprises:
[0081] The irradiation power under UV lamp is: 120W~140W;
[0082] The irradiation time is 0.75 to 1.5 hours. The rate of the polymerization reaction can be accelerated by this power and time. By precisely controlling the irradiation time and power, the start and stop of the polymerization reaction can be precisely controlled, which helps to achieve fine adjustment of the hydrogel structure.
[0083] In a preferred embodiment of the present invention, step S7 includes:
[0084] The immersion time is 1.5 to 18 hours. When the hydrogel is immersed in 1,2-propylene glycol, the original swelling balance of the hydrogel is broken, resulting in the volume shrinkage of the hydrogel, which promotes the entanglement between polymer chains and improves the modulus of the hydrogel. And through the immersion treatment, the hydrogel can maintain its mechanical elasticity and structural integrity in a cold environment. At the same time, the anti-swelling property of 1,2-propylene glycol can help the hydrogel maintain stability in a high humidity environment.
[0085] In order to better understand the present invention, the above method is described in detail below in conjunction with specific embodiments.
[0086] Example 1: Medical Grade Hydrogel Dressing
[0087] Group distribution ratio:
[0088] Polyvinyl alcohol: 6%
[0089] Acrylic acid: 7%
[0090] Silk protein: 10%
[0091] Modified carbon nanotubes: 0.03%
[0092] Deionized water: 35%
[0093] 1,2-Propanediol: 41.97%
[0094] Photoinitiator 2959: 0.1%.
[0095] Preparation steps:
[0096] Dissolve polyvinyl alcohol in deionized water and stir at 95 °C for 2 hours;
[0097] Add acrylic acid and photoinitiator 29590 and stir magnetically at room temperature for 30 minutes;
[0098] Slowly add silk protein and stir at high speed for 25 minutes;
[0099] The modified carbon nanotube powder was added with a small amount of deionized water and ultrasonicated for 3 minutes;
[0100] The carbon nanotube solution was added to the main mixture and magnetically stirred for 30 minutes;
[0101] Expose under a 130W UV lamp for 1 hour for light curing;
[0102] The photocured hydrogel was immersed in 1,2-propylene glycol for 12 h.
[0103] Embodiment 2: Antifreeze and sweat-resistant insole material
[0104] Group distribution ratio:
[0105] Polyvinyl alcohol: 8%
[0106] Acrylic acid: 6%
[0107] Silk protein: 8%
[0108] Modified carbon nanotubes: 0.04%
[0109] Deionized water: 38%
[0110] 1,2-Propanediol: 39.96%
[0111] Photoinitiator 2959: 0.1%.
[0112] Preparation steps:
[0113] Dissolve polyvinyl alcohol in deionized water and stir at 100 °C for 1.5 hours;
[0114] Add acrylic acid and photoinitiator 29590 and stir magnetically at room temperature for 25 minutes;
[0115] Slowly add silk protein and stir at high speed for 30 minutes;
[0116] Add a small amount of deionized water to the modified carbon nanotube powder and treat it with ultrasound for 4 minutes; add the carbon nanotube solution to the main mixed solution and stir it magnetically for 30 minutes;
[0117] Expose under a 140W UV lamp for 1.5 hours for light curing;
[0118] The photocured hydrogel was immersed in 1,2-propylene glycol for 18 h.
[0119] Example 3: Electronic skin sensor
[0120] Group distribution ratio:
[0121] Polyvinyl alcohol: 7%
[0122] Acrylic acid: 8%
[0123] Silk protein: 12%
[0124] Modified carbon nanotubes: 0.05%
[0125] Deionized water: 33%
[0126] 1,2-Propanediol: 39.95%
[0127] Photoinitiator 2959: 0.15%.
[0128] Preparation steps:
[0129] Dissolve polyvinyl alcohol in deionized water and stir at 95 °C for 2 hours;
[0130] Add acrylic acid and photoinitiator 29590 and stir magnetically at room temperature for 30 minutes;
[0131] Slowly add silk protein and stir at high speed for 30 minutes;
[0132] The modified carbon nanotube powder was added with a small amount of deionized water and ultrasonicated for 3 minutes;
[0133] The carbon nanotube solution was added to the main mixture and magnetically stirred for 30 minutes;
[0134] Expose under a 120W UV lamp for 1 hour for light curing;
[0135] The photocured hydrogels were immersed in 1,2-propylene glycol for 16 h.
[0136] Example 4: High-strength building materials
[0137] Group distribution ratio:
[0138] Polyvinyl alcohol: 5%
[0139] Acrylic: 10%
[0140] Silk protein: 15%
[0141] Modified carbon nanotubes: 0.02%
[0142] Deionized water: 30%
[0143] 1,2-Propanediol: 39.98%
[0144] Photoinitiator 2959: 0.2%.
[0145] Preparation steps:
[0146] Preparation steps:
[0147] Dissolve polyvinyl alcohol in deionized water and stir at 95 °C for 2 hours;
[0148] Add acrylic acid and photoinitiator 29590 and stir magnetically at room temperature for 30 minutes;
[0149] Slowly add silk protein and stir at high speed for 25 minutes;
[0150] The modified carbon nanotube powder was added with a small amount of deionized water and ultrasonicated for 3 minutes;
[0151] The carbon nanotube solution was added to the main mixture and magnetically stirred for 30 minutes;
[0152] Expose under a 140W UV lamp for 1 hour for light curing;
[0153] The photocured hydrogel was immersed in 1,2-propylene glycol for 1.5 h.
[0154] Comparative experiment 1: Mechanical properties comparison experiment purpose: to compare the performance differences in mechanical strength and elasticity between the hydrogel of the present invention and the control group.
[0155] Control group design
[0156] Control group A: hydrogel without modified carbon nanotubes;
[0157] Control group B: hydrogel without silk protein;
[0158] Control group C: commercially available medical grade hydrogel;
[0159] Experimental group: the hydrogel of the present invention, comprising modified carbon nanotubes and silk protein.
[0160] Experimental Materials:
[0161] Polyvinyl alcohol;
[0162] acrylic acid;
[0163] Silk protein;
[0164] Modified carbon nanotubes;
[0165] Photoinitiator 2959;
[0166] Deionized water;
[0167] 1,2-Propanediol;
[0168] Commercial medical grade hydrogel samples.
[0169] Experimental equipment:
[0170] Universal material testing machine;
[0171] Sample preparation mold;
[0172] Temperature controlled room.
[0173] Experimental steps:
[0174] Sample preparation:
[0175] Prepare hydrogel solutions for different control and experimental groups according to their respective formulas;
[0176] Pour the solution into a mold of the same size;
[0177] Light curing under specified conditions;
[0178] The light-cured samples were left at room temperature for 24 hours to ensure complete stabilization.
[0179] Mechanical testing:
[0180] The cured hydrogel samples were cut into standard sizes for testing;
[0181] Compression and tension testing using a universal materials testing machine;
[0182] The compression modulus, tensile strength, and elongation at break were recorded for each specimen.
[0183] Data recording and analysis:
[0184] Compare the mechanical properties data of each group of samples;
[0185] The performance improvement of the hydrogel of the present invention and the difference between it and the control group were analyzed.
[0186] The comparative experimental data are shown in Table 1:
[0187] Table 1 Hydrogel mechanical properties test results
[0188] sample Compression modulus (MPa) Tensile strength(MPa) Elongation at break (%) Control group A 0.52 1.03 120 Control group B 0.75 1.25 115 Control group C 1.20 1.50 150 Experimental Group 1.40 1.80 160 Control group A 0.48 0.98 125 Control group B 0.78 1.30 110 Control group C 1.22 1.55 148 Experimental Group 1.38 1.85 158
[0189] From the data in Table 1, we can get:
[0190] The results showed that the added modified carbon nanotubes and silk protein effectively enhanced the mechanical properties of the hydrogel. The volatility of the data also indicated the performance of each formula in terms of repeatability and consistency, providing a basis for further optimization of the formula and processing conditions.
[0191] Comparative experiment 2: Temperature tolerance test
[0192] Experimental purpose: To evaluate the performance of the hydrogel of the present invention under extreme temperature conditions.
[0193] Control group design
[0194] Control group A: traditional polyvinyl alcohol-based hydrogel;
[0195] Control group B: hydrogel containing the same concentration of acrylic acid but without 1,2-propylene glycol;
[0196] Experimental group: the hydrogel of the present invention, comprising modified carbon nanotubes, 1,2-propylene glycol, silk protein, etc.
[0197] Experimental Materials:
[0198] Various hydrogel components;
[0199] Temperature control box;
[0200] Experimental equipment;
[0201] Temperature control box;
[0202] Mechanical properties testing equipment;
[0203] Dimensional measuring tools.
[0204] Experimental steps:
[0205] Sample preparation:
[0206] Prepare hydrogel solutions for different control and experimental groups according to their respective recipes;
[0207] The solution is poured into a mold and processed under specified curing conditions to form a hydrogel sheet of standard size;
[0208] All samples were left at room temperature for 24 hours to reach a stable state.
[0209] Temperature exposure:
[0210] All samples were placed in temperature-controlled boxes set at -10°C and 50°C, and exposed to each temperature for 24 hours;
[0211] Do this in batches to ensure that each sample undergoes the same temperature treatment.
[0212] Performance Test:
[0213] After completing the temperature exposure, the compression modulus and elongation at break of each sample were measured immediately;
[0214] Record any visible physical changes such as deformation, softening, or embrittlement.
[0215] The comparative experimental data are shown in Table 2:
[0216] Table 2 Hydrogel temperature tolerance test results
[0217]
[0218]
[0219] From the data in Table 2, we can get:
[0220] The data in the table show that the experimental group exhibits higher compression modulus and better elongation at break under extreme temperature conditions, especially maintaining better structural stability and mechanical properties under low temperature conditions, indicating that the hydrogel of the present invention has excellent temperature tolerance. The control group exhibits significant performance degradation, such as softening and embrittlement, especially under high temperature conditions, while the experimental group exhibits better temperature resistance and environmental adaptability.
[0221] Comparative experiment 3: biocompatibility test
[0222] Purpose:
[0223] The performance difference in biocompatibility between the hydrogel of the present invention and the hydrogel of the control group was evaluated.
[0224] Control group design:
[0225] Control group A: hydrogel without silk protein;
[0226] Control group B: conventional medical silicone;
[0227] Experimental group: the hydrogel of the present invention, comprising modified carbon nanotubes, silk protein, etc.
[0228] Experimental Materials:
[0229] Various hydrogel ingredients:
[0230] human skin fibroblasts;
[0231] Cell culture related reagents and equipment.
[0232] Experimental equipment:
[0233] Cell culture incubator;
[0234] microscope;
[0235] MTT analysis tool;
[0236] ELISA reader.
[0237] Experimental steps:
[0238] Sample preparation:
[0239] Prepare hydrogel solutions for different control and experimental groups according to their respective recipes;
[0240] Pour the solution into a mold and perform a curing process;
[0241] The solidified hydrogel was cut into small pieces suitable for cell culture.
[0242] Cell culture:
[0243] Human skin fibroblasts were used for testing. The cells were seeded into culture dishes containing each group of hydrogel samples under sterile conditions;
[0244] The cells were cultured in a cell culture incubator at 37°C and 5% CO2.
[0245] MTT biocompatibility test:
[0246] After 48 hours of culture, the cell activity was tested using MTT reagent. MTT reagent can be reduced by mitochondrial enzymes in living cells to form purple methylamine;
[0247] The optical density of methylamine formed in each sample was measured using a microplate reader to assess cell viability and growth.
[0248] The comparative experimental data are shown in Table 3:
[0249] Table 3 MTT test results of hydrogel biocompatibility
[0250]
[0251]
[0252] From the data in Table 3, we can get:
[0253] The data in the table show that the hydrogel in the experimental group is close to the standard control group of conventional medical silicone in the cell activity test, indicating that it has good biocompatibility. Although the control group A performed well, it was slightly lower than the experimental group and control group B, indicating that the addition of silk protein helps to improve the biocompatibility of the hydrogel.
[0254] Comparative experiment 4: durability and stability test
[0255] Experimental purpose: To test the stability and durability of the hydrogel of the present invention and the hydrogel of the control group under long-term storage or repeated use conditions.
[0256] Control group design:
[0257] Control group A: traditional polyvinyl alcohol-based hydrogel;
[0258] Control group B: commercially available antifreeze hydrogel (used as a high standard control for durability);
[0259] Experimental group: the hydrogel of the present invention, comprising modified carbon nanotubes, 1,2-propylene glycol, silk protein, etc.
[0260] Experimental Materials:
[0261] Various hydrogel components;
[0262] long-term storage facilities;
[0263] Experimental equipment;
[0264] Constant temperature and humidity test chamber;
[0265] Mechanical properties testing equipment;
[0266] UV light aging test equipment.
[0267] Experimental steps:
[0268] Sample preparation:
[0269] Prepare hydrogel solutions for different control and experimental groups according to their respective recipes;
[0270] Pour the solution into a mold and perform a curing process;
[0271] The cured hydrogel was cut into standard test pieces.
[0272] Long term storage test:
[0273] All samples were stored in a constant temperature and humidity test chamber set at 25°C and 50% relative humidity for 12 months;
[0274] Conduct performance tests every 3 months and record the data.
[0275] Cyclic freeze-thaw test:
[0276] The samples were subjected to at least 10 cycles of freeze-thaw testing between -20°C and 25°C;
[0277] The mechanical properties and visible physical changes of the samples were measured after each cycle.
[0278] UV aging test:
[0279] Place the samples in a UV aging test device to simulate long-term sunlight exposure;
[0280] The exposure was continued for 200 hours, during which the samples were regularly checked for color changes and physical properties.
[0281] The comparative experimental data are shown in Table 4:
[0282] Table 4 Hydrogel durability and stability test results
[0283]
[0284]
[0285] From the data in Table 4, we can get:
[0286] This data table shows that the experimental group exhibits better stability and durability than the control group A in long-term storage, freeze-thaw cycle and UV aging tests, and is close to and exceeds the performance of the high standard control group B. This reflects that the improved formula of the hydrogel of the present invention provides better environmental resistance, especially stability and durability under extreme conditions.
[0287] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An antifreeze and sweat-resistant hydrogel with adjustable mechanical modulus, characterized in that: include: Polyvinyl alcohol: 4% to 8%; Acrylic acid: 5% to 10%; Silk protein: 8%-15%; Modified carbon nanotubes: 0.01% to 0.05%; Deionized water: 30% to 40%; 1,2-Propanediol: 35%~45%.
2. The antifreeze and sweat-resistant hydrogel with adjustable mechanical modulus according to claim 1, characterized in that: The hydrogel also includes photoinitiator 2959: 0.05% to 0.2%.
3. A method for preparing an antifreeze and sweat-resistant hydrogel with adjustable mechanical modulus, characterized in that: Using the antifreeze and sweat-resistant hydrogel with adjustable mechanical modulus according to any one of claims 1 to 2 comprises the following steps: S1. Dissolve polyvinyl alcohol in deionized water and stir to ensure that the polyvinyl alcohol is completely dissolved; S2, adding acrylic acid and photoinitiator 2959 to the above solution; S3, slowly add silk protein; S4, adding the modified carbon nanotube powder into deionized water; S5, adding the modified carbon nanotube solution obtained in step S4 to the mixed solution in step S3; S6, placing the mixed solution under ultraviolet light to perform a photocuring reaction; S7. Soak the photocured hydrogel in 1,2-propylene glycol to adjust and control the mechanical modulus of the final hydrogel.
4. The method for preparing an antifreeze and sweat-resistant hydrogel with controllable mechanical modulus according to claim 3, characterized in that: The S1 step includes: Stirring temperature: 95℃~100℃; Stirring time: 1.5 to 2.5 hours.
5. The method for preparing an antifreeze and sweat-resistant hydrogel with controllable mechanical modulus according to claim 3, characterized in that: The S2 step includes: Use magnetic stirring under a warm room to thoroughly mix the acrylic acid and photoinitiator 2959; The magnetic stirring time is 25 to 35 minutes.
6. The method for preparing an antifreeze and sweat-resistant hydrogel with controllable mechanical modulus according to claim 3, characterized in that: The S3 step includes: Continue to slowly add silk protein under high-speed stirring to ensure that the silk protein is evenly dispersed in the solution; High-speed stirring time is: 25 to 35 minutes.
7. The method for preparing an antifreeze and sweat-resistant hydrogel with adjustable mechanical modulus according to claim 3, characterized in that: The S4 step includes: Using an ultrasonic device to treat the added modified carbon nanotube powder to obtain a uniformly dispersed modified carbon nanotube solution; The processing time of ultrasonic equipment is: 2 to 5 minutes.
8. The method for preparing an antifreeze and sweat-resistant hydrogel with controllable mechanical modulus according to claim 3, characterized in that: The S5 step includes: Mixing the modified carbon nanotube solution and the mixed solution thoroughly under magnetic stirring at room temperature; The magnetic stirring time is 25 to 35 minutes.
9. The method for preparing an antifreeze and sweat-resistant hydrogel with controllable mechanical modulus according to claim 3, characterized in that: The S6 step includes: The irradiation power under UV lamp is: 120W~140W; The irradiation time is: 0.75 to 1.5 hours.
10. The method for preparing an antifreeze and sweat-resistant hydrogel with adjustable mechanical modulus according to claim 3, characterized in that: The S7 step includes: The soaking time is: 1.5 to 18 hours to achieve the expected modulus regulation, antifreeze and sweat resistance effects.
